Strategies for Enhancing Home Economics Teachers’ Service Delivery in Some Selected Public Secondary Schools in Lagos State - Kemi P. Ogbonna; Ukamaka G. Okwume; Francisca N. Onyeka; Temitope F. Ogabi (International Journal of Home Economics, Hospitality and Allied Research)
This study determined the strategies for enhancing home economics teachers’ service delivery in some selected public secondary schools in Yaba, Lagos State. The study adopted a descriptive survey design. Population for the study was 150 and the sample size was 50. Purposive sampling technique was adopted. Structured questionnaires were the instrument used for data collection. Data collected were analyzed using mean and standard deviation. Findings revealed that some of the factors that have negative impacts on Home Economics teachers service delivery are obsolete curriculum that are not in tune with current realities, lack of meaningful job schedule, lack of proper planning and provision of needed technological tools, facilities and equipment needed foreffective teaching and learning of home economics, lack of proper procedures for measuring the growth of each individual teacher and student performance, inability to make result driven evaluation that would help teachers appreciate their roles as home economist and lack of clear understanding of the subject matter. It was concluded that that employees provides favorable and satisfying working conditions, teachers should be an embodiment of a constant search for updated knowledge in their various fields. Amongst the recommendations made were that there should be training and re-training for teachers, increased remuneration so as to enhance their service delivery and only professionally trained Home Economist should be allowed to teach Home Economics as a subject.